Effects of Zinc Sulphate Used as an Elicitor on Superoxide Dismutase, Peroxidase and Total Phenolic Compounds of Pepper Calluses - Cemil İşlek; Bengü Türkyılmaz Ünal; Sinan Aydın (Turkish Journal of Agriculture: Food Science and Technology)
The amount of secondary metabolites can be increased with different elicitor applications in vitro. It has been determined that zinc sulphate significantly increases the amount of capsaicin in the cell culture of red hot pepper. It is important to determine how the metal applied as elicitor will have an effect on plant metabolism. In the study, it was aimed to determine the effects of zinc sulphate (ZnSO4) applied to the cell suspension cultures of pepper seeds at different concentrations (0.1 M, 0.2 M, 0.4 M) and for periods (24, 48, 72 hours) on the total protein and phenolic substance amounts, and superoxide dismutase-peroxidase enzyme activities of pepper calluses. It was observed that the amount of protein increased, superoxide dismutase and peroxidase enzyme activities decreased, and the total amount of phenolic substance increased especially in 72 hours of treatment where zinc was applied as elicitor. These results show that ZnSO4 can be used as an abiotic elicitor in plant cell culture media.